2019
DOI: 10.1051/0004-6361/201834548
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of magnetic transients in a solar active region plage

Abstract: Context. Densely packed coronal loops are rooted in photospheric plages in the vicinity of active regions on the Sun. The photospheric magnetic features underlying these plage areas are patches of mostly unidirectional magnetic field extending several arcsec on the solar surface. Aims. We aim to explore the transient nature of the magnetic field, its mixed-polarity characteristics, and the associated energetics in the active region plage using high spatial resolution observations and numerical simulations. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…This explanation in reasonably, given that cancellation events have been observed on the solar surface in active regions (e.g. Green et al 2011, Tiwari et al 2019, in active region plage (Chitta et al 2019) and even in quiet Sun regions (Wang Jingxiu et al 1988).…”
Section: What Happens To the Flux?mentioning
confidence: 86%
“…This explanation in reasonably, given that cancellation events have been observed on the solar surface in active regions (e.g. Green et al 2011, Tiwari et al 2019, in active region plage (Chitta et al 2019) and even in quiet Sun regions (Wang Jingxiu et al 1988).…”
Section: What Happens To the Flux?mentioning
confidence: 86%
“…8a). It is possible that a small-scale weak opposite-polarity magnetic element is present, but remained undetected in HMI observations as a result of a combination of the moderate spatial resolution and sensitivity of the instrument (e.g., Chitta et al 2017bChitta et al , 2019. It is also possible that the burst is triggered by a component magnetic reconnection within the unipolar magnetic patch.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of time-averaging the magnetic field only over the initial 30 min ensures that we do not misclassify unipolar cases as mixed cases in events when new flux emergence brings up persistent opposite polarity in the region after the heating event peak. At the same time we might underestimate the number of mixed cases when the opposite polarity is weak and transient in the first 30 min window (see examples of transient opposite-polarity patches in unipolar regions presented in Chitta et al 2019).…”
Section: A2 Analysis Of Magnetic Roots Of Impulsive Heating Eventsmentioning
confidence: 98%
“…Here we conducted an extensive statistical analysis of 137 impulsive heating events from seven different active regions covering 404 h of solar evolution and found that about 73% of cases (101 out of 137) have mixed polarity magnetic fields with flux content over 10 17 Mx at the footpoints of hot loops. Due to the limited spatial resolution and sensitivity of the HMI instrument, the number of mixed events is likely to be an underestimate as shown in examples where the mixed polarity nature of the fields remains hidden to HMI observation (Chitta et al 2017a(Chitta et al , 2019.…”
Section: A21 Degree Of Magnetic Flux Imbalance In Mixed Polarity Ementioning
confidence: 99%
See 1 more Smart Citation